2015
DOI: 10.1097/jan.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Treatment Options for Co-Occurring Methamphetamine Use Disorders and Depression

Abstract: Co-occurring methamphetamine use and depression interferes with treatment outcomes. Female methamphetamine users are known to have higher rates of depression than male methamphetamine users, although this is also true for the general population. There are limited treatment options for the management of depression among methamphetamine users. In this integrative review, we summarize data on treatment strategies for co-occurring depression and methamphetamine use disorders. English-language articles were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…For example, men may experience strong urges to use MA in response to negative affect, whereas women may place themselves in risky social situations (i.e., contexts where their peers are drinking or using) as they seek support for coping with negative affect. Understanding the specific trajectories and behaviors that differentiate men from women in their responses to negative affect may be valuable as a means of designing much needed gender-specific interventions (Hellem et al, 2015). For current alcohol users, women may be more susceptible to alcohol craving in response to negative mood induction than men (Rubonis et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, men may experience strong urges to use MA in response to negative affect, whereas women may place themselves in risky social situations (i.e., contexts where their peers are drinking or using) as they seek support for coping with negative affect. Understanding the specific trajectories and behaviors that differentiate men from women in their responses to negative affect may be valuable as a means of designing much needed gender-specific interventions (Hellem et al, 2015). For current alcohol users, women may be more susceptible to alcohol craving in response to negative mood induction than men (Rubonis et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences in psychiatric comorbidity have also been observed, where women with MUD are more likely than men to report symptoms of depression (Hser et al, 2005; Dluzen & Liu, 2008) and meet diagnostic criteria for major depressive disorder (MDD; Glasner-Edwards et al, 2009). Additionally, women with MUD appear more likely to report anxiety (Salo, et al, 2011), particularly social anxiety disorder (Glasner-Edwards et al, 2010a); however, less is known about the treatment of comorbid MUD and mood or anxiety disorders (Hellem, Lundberg, & Renshaw, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Also, in this study, it was concluded that the symptoms of psychotic and mood symptoms could be important in both recurrence and prognosis of patients with methamphetamine abuse (5). On the other hand, due to the high comorbidity of depressive symptoms in people who abuse methamphetamine, it is hypothesized that the risk of other psychiatric disorders may underlie addiction or relapse of methamphetamine use (17).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that short-and long-term methamphetamine use is associated with depression (DiMiceli, Sherman, Aramrattana, Sirirojn, & Celentano, 2016;Kalechstein et al, 2000;Nakama et al, 2008;Semple, Patterson, & Rant, 2009;Shoptaw, Peck, Redbackm, & Rotheram-Fuller, 2003) and that individuals with depression may self-medicate with methamphetamine (Hellem, Lundberg, & Renshaw, 2015;McKetin, Lubman, Lee, Ross, & Slade, 2011;Semple, Zians, Strathdee, & Patterson, 2007). The relationship between the symptoms of depression and methamphetamine intoxication and withdrawal complicates diagnosing major depressive disorder (MDD; Langa s, Malt, & Opjordsmoen, 2011) and measuring depression severity in methamphetamine users due to overlap in symptoms of depression and intoxicating effects of methamphetamine.…”
Section: Introductionmentioning
confidence: 99%